Strategi Marketing Public Relation Pt Asuransi Takaful Keluarga Dalam Pemasaran Produk Al-Khairat - Atika; Marlina (CV. Ulil Albab Corp, 2022)
Al-Khairat product is a program from PT Asuransi Takaful Keluarga in providing benefits partial in the form of compensation payments to heirs if the participant is destined to die during the agreement period. This product provides 100% Basic Takaful Benefits that will be paid if the Participant dies within the validity period of the Policy, and also Personal accident compensation, or suffers a permanent record (total and) due to an accident. This study aims to (1) determine the proper role of public relations in marketing Al-Khairat products at PT Asuransi Takaful Keluarga Setia Budi Medan Branch. (2) To find out how the strategy of Public Relations to get used to being future-oriented in marketing problems to the community so that the communication delivered is right on the desired target. The approach used in this research is a qualitative approach, coupled with data collection techniques through interviews and literature study. Keywords: Public Relations, Al-Khairat Products, marketing